Selection of internal standards for accurate quantification of complex lipid species in biological extracts by electrospray ionization mass spectrometry—What, how and why? - Wang, Miao; Wang, Chunyan; Han, Xianlin (Mass spectrometry reviews, 2017)
Lipidomics is rapidly expanding because of the great facilitation of recent advances in, and novel applications of, electrospray ionization mass spectrometry techniques. The greatest demands have been for successful quantification of lipid classes, subclasses, and individual molecular species in biological samples at acceptable accuracy. This review addresses the selection of internal standards in different methods for accurate quantification of individual lipid species. The principles of quantification with electrospray ionization mass spectrometry are first discussed to recognize the essentials for quantification. The basics of different lipidomics approaches are overviewed to understand the variables that need to be considered for accurate quantification. The factors that affect accurate quantification are extensively discussed, and the solutions to resolve these factors are proposed‐largely through addition of internal standards. Finally, selection of internal standards for different methods is discussed in detail to address the issues of what, how, and why related to internal standards. We believe that thorough discussion of the topics related to internal standards should aid in quantitative analysis of lipid classes, subclasses, and individual molecular species and should have big impacts on advances in lipidomics. © 2016 Wiley Periodicals, Inc. Mass Spec Rev 36:693–714, 2017